Hydrothermally assisted synthesis of YMnO3 - Branković, Z.; Branković, G.; Počuča-Nešić, M.; Marinković Stanojević, Z.; Žunić, M.; Luković Golić, D.; Tararam, R.; Cilense, M.; Zaghete, M. A.; Jagličić, Z.; Jagodič, M.; Varela, J. A. (My University, 2015)
In this work single phase hexagonal YMnO3 powders were prepared starting from Y(CH3COO)3·xH2O, Mn(CH3COO)2·4H2O, KMnO4 and KOH using methods of conventional (280°C for 6h) or microwave assisted hydrothermal synthesis (200°C for 2h) followed by calcination at 1200°C for 2h. According to FESEM analysis the calcined powders consisted of submicronic YMnO3 particles, which were uniform in shape and size. Ceramic samples were obtained by sintering the as-synthesized powders at 1400°C for 2h. XRD analysis confirmed the presence of the single phase hexagonal YMnO3. SEM analysis showed a dense and homogeneous microstructure with typical inter- and intra-grain cracks. Magnetic measurements indicated ferrimagnetic properties that were explained by non-stoichiometry of the obtained compound and an excess of manganese that was confirmed by ICP analysis.
Keywords: Hydrothermal synthesis; Magnetic measurements; Phase evolution; Yttrium manganite